The scope of medical harm within the framework of civil liability - Mezher, Akram Subhi (Journal of Economic, Administrative and Legal Sciences, 2021)
Due to the enormous scientific developments and technological advances in all areas of life, It has become very important to follow these developments, so that they must be surrounded by legislative guarantees guaranteeing respect and care for the human personality as much as possible in all circumstances. There is no doubt that modern medical science has become providing services to humanity with distinguished services, and medicine has become more effective and more ambitious than it was in the past and at the same time more dangerous as any scientific progress, where medicine has witnessed a significant and significant development in recent years, making many acknowledge that what happened The development and progress in the medical fields during the last fifty years exceeds in its importance what happened during the twenty centuries of medical science.And medicine still comes every day with what is new in all its specialties, so that the most important thing that distinguishes it is the positivity and effectiveness that made him exceed the limits of his original mission, which is prevention and treatment of diseases, to also include the fulfillment of human desires in many non-therapeutic areas, as is the case, for example, in Plastic and other surgeries.The Department of Medical Sciences has expanded and renewed today, as have the tools and methods used by the doctor in treating the patient, and this is what made the patient think often that the doctor could not fail, or disappointment in his therapeutic or surgical intervention, until he knowingly and consciously confused his right to medical care and his right to the safety of his health and the guarantee of recovery, in many cases where the doctor or surgeon fails to treat or surgery, the patient does not hesitate in the percentage of error and default or the cause of failure and failure to this doctor or that surgeon, asking him to compensate for the damage caused to him. Hence, it is not surprising that doctors sense a degree of injustice when applying to their relationship with their patients the general rules of civil responsibility. In many cases, the doctor makes sincere and vigilant efforts to treat the patient, but in spite of this the patient suffers untold damage. However, this error is attributed to the doctor.
Keywords: medical error; nature of medical damage; medical civil liability; the doctor; the injured patient